Agricultural Engineering Students' Segmentation in Relation to Their Attitudes towards English-Medium Instruction - Ana Isabel Carrapiso; Elena González; María Jesús Petrón; Francisco Pérez-Nevado; Paula Gaspar (MDPI AG, 2023)
The School of Agricultural Engineering has been involved in English-medium instruction (EMI) within the framework of the internationalization strategy of the University of Extremadura (Spain). Several years after these actions were initiated, it has become necessary to analyze them, with the main objective of researching the attitude of the students towards it, keeping the focus on finding common trends. With this aim, a segmentation of the students was carried out based on a questionnaire that included aspects related to their attitudes towards English-medium instruction, their socio-demographic characteristics and the program they were enrolled in. A total of 251 students were surveyed, and the data were analyzed by performing a multiple correspondence analysis and a cluster analysis. They revealed three typologies of students with clearly different underlying features, especially related to the program and year in which they were enrolled, their age and English level, and their perceived skills. The main conclusion is that the multivariate techniques applied are useful tools to identify groups of students with different features in the EMI frame, which may facilitate the launch of specific actions focused on the needs and expectations of each group to ensure that EMI programs and students achieve their goals.